ZEB2 haploinsufficient Mowat-Wilson syndrome induced pluripotent stem cells show disrupted GABAergic transcriptional regulation and function - Schuster, Jens; Klar, Joakim; Khalfallah, Ayda; Laan, Loora; Hoeber, Jan; Fatima, Ambrin; Sequeira, Velin Marita; Jin, Zhe; Korol, Sergiy V.; Huss, Mikael; Nordgren, Ann; Anderlid, Britt Marie; et al. (Frontiers in Molecular Neuroscience, 2022)
Mowat-Wilson syndrome (MWS) is a severe neurodevelopmental disorder caused by heterozygous variants in the gene encoding transcription factor ZEB2. Affected individuals present with structural brain abnormalities, speech delay and epilepsy. In mice, conditional loss of Zeb2 causes hippocampal degeneration, altered migration and differentiation of GABAergic interneurons, a heterogeneous population of mainly inhibitory neurons of importance for maintaining normal excitability. To get insights into GABAergic development and function in MWS we investigated ZEB2 haploinsufficient induced pluripotent stem cells (iPSC) of MWS subjects together with iPSC of healthy donors. Analysis of RNA-sequencing data at two time points of GABAergic development revealed an attenuated interneuronal identity in MWS subject derived iPSC with enrichment of differentially expressed genes required for transcriptional regulation, cell fate transition and forebrain patterning. The ZEB2 haploinsufficient neural stem cells (NSCs) showed downregulation of genes required for ventral telencephalon specification, such as FOXG1, accompanied by an impaired migratory capacity. Further differentiation into GABAergic interneuronal cells uncovered upregulation of transcription factors promoting pallial and excitatory neurons whereas cortical markers were downregulated. The differentially expressed genes formed a neural protein-protein network with extensive connections to well-established epilepsy genes. Analysis of electrophysiological properties in ZEB2 haploinsufficient GABAergic cells revealed overt perturbations manifested as impaired firing of repeated action potentials. Our iPSC model of ZEB2 haploinsufficient GABAergic development thus uncovers a dysregulated gene network leading to immature interneurons with mixed identity and altered electrophysiological properties, suggesting mechanisms contributing to the neuropathogenesis and seizures in MWS.